IN SEARCH OF RELIABLE KNOWLEDGE: REFLECTION IN THE LIGHT OF THE THINKING OF JOHN ZIMAN - Elizabeth Teixeira; Horácio Pires Medeiros (Universidade Federal do Paraná, 2011)
A reflective study, based on content analysis, which aimed to widen discussion among Nursing researchers on the subject of the challenges of scientific literature production, to attain a degree of knowledge which is reliable or nearly so, in the light of the thinking of John Ziman. The degree of knowledge's reliability passes through the obtaining of consensus between pairs, the organicity of production and the communicative act, among other aspects. The challenges to researchers are not only theoretical-methodological, but also epistemological and social. It is suggested to be attentive to limits (and absences) and possibilities (emerging perspectives), in order to strengthen and contribute to the knowledge produced, disseminated and in expansion in Brazilian Nursing.